Analysis of Society Conditions/Reality During Chinese Feudal Era in the Novel Liaozhai Zhiyi - Chongjie, Chen; Yoan, Yoan; Kelly, Kelly (Bina Nusantara University, 2010)
Liaozhai Zhiyi is a compilation of short stories created by the Qing Dynasty novelist, Pu Songling. The main concept is not centered on regular ghost stories, but the author told a story on real life and the fantasy world by describing realities of society life in the feudal era. The author, through stories in Liaozhai Zhiyi, analyses social reality in their education, politics, love, economic and moral aspects. The author of Liaozhai Zhiyi uses of a lot of stories concerning fox spirits, ghosts, and other types of spirits in portraying his critics and anger towards incidents happening in feudal China. Analysis shows that Liaozhai Zhiyi broadly depicts social reality happening in feudal era in education, politics, love, economic and moral aspects. Liaozhai Zhiyi also criticizes the corrupt government official examination scheme, and the crime and decadence of the feudal government. In contrast, the stories also praised the freedom of young men and women seeking love in marriage, endorsing young men and women to reject arranged marriages, showing women in the economic independence and social advancement, and summed up the lessons of social life.